Left Ventricular Pseudoaneurysm Caused by Radiofrequency Catheter Ablation: From Diagnosis to Treatment With Multimodality Imaging. (September 2021) - Nicolazzi, Joseph; Grizzard, John; Kasirajan, Vigneshwar; Ellenbogen, Kenneth; Markley, Roshanak
Abstract : Supplemental Digital Content is available in the text.